Analisis Social Return on Investment (SROI) pada Program Svara Resonance: Digitalisasi dan Audisi Musisi Jalanan di Surabaya - Susanti; Premananto, Gancar Candra (Bhakti Persada Jurnal Aplikasi IPTEKS, 2025)
Digitalization training for street musicians is very important in achieving sustainable development goals. Svara Resonance is a digitalization training and audition event organized by master's degree students in management at Airlangga University. This event is conducted to provide digitalization training and hold auditions for street musicians in Surabaya. For street musicians, art is a means of self-expression, allowing them to develop as they freely express their work. The method for calculating the Social Return on Investment (SROI) ratio involves 6 stages. Based on the calculation of the SROI ratio, every Rp 1 invested in the Svara Resonance program for the digitalization and audition of street musicians generates a benefit of Rp 42. This SROI value results in a quite high return. Implementing the Svara Resonance program to digitize and support street musicians provides significant benefits to all stakeholders.